2D silhouette animation: Expression of emotion through animated batik background in animation project ‘Part Behind’ / Nurul Amin Ahmad - Ahmad, Nurul Amin (Faculty of Film, Theatre and Animation, 2014)
The aim of this study is to create two dimensional (2d) animation by integrating silhouette with batik as animated background. In line with the public interest to support Malaysia’s heritage, this study attempts to ascertain the outcome and effectiveness of applying the art of batik into animated work. Recent studies in animation have highlighted the important roles of background in specific scenes to support the storytelling. The background is concerned with not only the detail and color that used, but also the ways in which it appeals and conveys to the viewer as information, In this project animation Part Behind, using both batik and silhouette as the main formula can realize its capability as the project’s experiment main reason of the conduct, in the end, the result is depending on gathering data from the viewers’ response to further prove whether batik can really be applied through animation. This study focuses on the concept, idea and animating style so as to explore the efficient ways so that batik and shadow puppet can be adapted into digital medium such as animation